Ecobiometría del diámetro de la vaina del nervio óptico en potros neonatos de raza Criollo Colombiano - Velásquez Tuberquia, Daniel (2025)
The aim of this study was to determine the normal values of the optic nerve sheath diameter in healthy neonatal Criollo Colombiano foals through ultrasonography. Twelve individuals (7 males and 5 females) were evaluated. The distance from the rostral to the caudal edge, and from the medial to the lateral edge of the optic nerve sheath was measured. Correlations were made between this diameter and the variables age, weight and sex of the neonates. The mean diameter of the optic nerve sheath was 0.33 cm for the right eye and 0.34 cm for the left eye. No significant associations (p>0.05) were found between this diameter and the age, body weight and sex of the neonates.